2021
DOI: 10.37201/req/123.2020
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal infection in renal transplant: two case reports and a literature review

Abstract: The first case was a 64-year-old woman with chronic kidney failure secondary to nephroangiosclerosis and nonsteroidal anti-inflammatory drug use, who received a kidney transplant in July 2017. Immunosuppressive therapy included prednisone, tacrolimus, and mycophenolate. In October 2018, the patient was admitted for a two-week history of progressive cephalea, diplopia and occasional speech problems, although the patient remained afebrile. Routine serum chemistry was normal, except for creatinine 2.75 mg/dL and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, the study revealed high acute high mortality rates in cryptococcemia patients with more than 10% of the patients dying before the availability of culture results [ 6 ]. Few case reports have described cryptococcemia in solid organ transplant patients [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the study revealed high acute high mortality rates in cryptococcemia patients with more than 10% of the patients dying before the availability of culture results [ 6 ]. Few case reports have described cryptococcemia in solid organ transplant patients [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In solid organ transplant patients, Cryptococcus neoformans infection usually occurs in the late post-transplantation period, typically over 12 months after the transplantation. Primary acquisition upon transplantation or reactivation of a dormant infection are two possible causes of this infection [ 8 , 9 ]. In our case, the infection appeared five years after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation